Análise de faltas em sistemas trifásicos a dois fios - Santos, Leonardo Felipe da Silva dos (2023)
The protection system is essential for the distribution of electrical energy, whether in rural or urban areas. During rural network expansions, the cost of a three-phase network can hinder the implementation of the project, limiting consumer access to an MRT network (single-phase with earth return) or MRN network (single-phase with neutral return). Recent studies have proposed the development of an innovative three-phase network known as the TPTW system (twowire three-phase), which utilizes the earth as a phase conductor. This approach has proven to be financially viable for installing three-phase networks in rural areas, as it leverages existing infrastructure and has no restrictions on single-phase power. In this study, a methodology was proposed for calculating short-circuits in a non-conventional two-wire three-phase system (TPTW). Additionally, an evaluation of the short-circuit calculations was conducted through simulations in the TPTW system. A validation process was also performed for the fuse-link models by comparing manufacturer data with values obtained in this study. Ultimately, this study validated the equations and the protection scheme for the TPTW system using fuse-links. It is worth noting that the TPTW system offers greater social and economic added value compared to the conventional three-phase system currently available for rural networks.